A Analisis Pembebanan Statis pada Chassis Electric Vehicle Race Car Menggunakan Metode FEA pada Autodesk Inventor: - - Danendra Rizky Ramadhan; Yusep Sukrawan; Tatang Permana; Gilang Ciptadi Mahatkarsa; Ibnu Mubarak (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
The rapid advancement of electric vehicle technology has created a growing necessity for chassis structures that are robust, weight-efficient, and engineered to meet stringent safety standards in order to optimize the performance of eco-friendly racing vehicles. This research was conducted to assess the structural integrity of the chassis in an Electric Vehicle Race Car when subjected to static load conditions. The analytical approach adopted in this study is the Finite Element Analysis (FEA) method, utilizing Autodesk Inventor software as the primary simulation tool. Two distinct load scenarios were applied during testing, specifically 70 kg and 100 kg, to obtain output values of Von Mises Stress, Displacement, and Safety Factor. The simulation outcomes revealed that both the Von Mises Stress and Displacement values remained within the permissible safety threshold of the selected material, while the Safety Factor value successfully surpassed the minimum design benchmark. Consequently, the chassis developed in this study is deemed to possess sufficient structural strength and rigidity, confirming its suitability for implementation in electric-powered racing vehicles.